2022
DOI: 10.1093/braincomms/fcac142
|View full text |Cite
|
Sign up to set email alerts
|

In vivo myelin imaging and tissue microstructure in white matter hyperintensities and perilesional white matter

Abstract: White matter hyperintensities negatively impact white matter structure and relate to cognitive decline in aging. Diffusion tensor imaging detects changes to white matter microstructure, both within the white matter hyperintensity and extending into surrounding (perilesional) normal appearing white matter. However, diffusion tensor imaging markers are not specific to tissue components, complicating interpretation of previous microstructural findings. Myelin water imaging is a novel imaging technique that provid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(40 citation statements)
references
References 60 publications
4
36
0
Order By: Relevance
“…The association in the NAWM may potentially reflect mild vascular damage and an early, pre-lesional role for FW in affecting cognitive function. 18, 26 Apart from the significant FW-cognition relationship, we observed that FW (but not FW-adjusted FA) mediated the association between PET and executive function in WMH. In contrast, lower FW-adjusted FA only showed a weak relationship with lower MoCA score within WMH and with lower MMSE score within NAWM (the sensitivity of MoCA to WMH may be related to its wider application as a screening tool for vascular cognitive impairment by covering domains of executive function) 55 .…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…The association in the NAWM may potentially reflect mild vascular damage and an early, pre-lesional role for FW in affecting cognitive function. 18, 26 Apart from the significant FW-cognition relationship, we observed that FW (but not FW-adjusted FA) mediated the association between PET and executive function in WMH. In contrast, lower FW-adjusted FA only showed a weak relationship with lower MoCA score within WMH and with lower MMSE score within NAWM (the sensitivity of MoCA to WMH may be related to its wider application as a screening tool for vascular cognitive impairment by covering domains of executive function) 55 .…”
Section: Discussionmentioning
confidence: 61%
“…First, while demyelinating fibers are an early feature in AD, 5 their direct effects on diffusion may be less pronounced in a sample enriched for SVD. 18, 40 Indeed, our group has previously shown that WM disease may primarily reflect chronic vasogenic edema (blood-brain barrier [BBB] leakage) or perivascular stasis (compromised circulation of interstitial fluid) induced by venous collagenosis and chronic hypoperfusion; 22, 23, 42 which may be a trigger of downstream neuroinflammation, damage to myelin membranes with potential formation of intramyelinic fluid-filled vacuoles, and axonal (Wallerian) degeneration due to cortical neuronal injury in cases with concomitant AD pathology. 40, 41, 43 Second, previous autopsy studies reported no PiB staining/binding to WM tracts, 3, 10 suggesting that demyelination alone does not account for the reduced PET signal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations